Anaesthetic performance of AQUI-S and 2-phenoxyethanol in fish for field applications - Jasmin C. Martino; Iain M. Suthers; Jessica Nguyen; Daniel E. Hewitt; Suzanna M. Evans; Hayden T. Schilling (Reviews in Fish Biology and Fisheries, 2026)
Ethical handling of fish in ecological research requires anaesthetic methods that are effective, practical, and adaptable for a diversity of field conditions. Estuarine environments, in particular, present challenges due to their fluctuating water chemistry. To improve our understanding of anaesthetic performance for field conditions, we compared AQUI-S, a commonly used clove oil-based anaesthetic, and 2-phenoxyethanol, a cost-effective alternative. First, we tested their influence on water pH across a range of baseline pH levels. We then conducted controlled trials on a representative Australian estuarine species (common hardyhead; Atherinomorus vaigiensis) , assessing induction, recovery, and euthanasia outcomes across increasing concentrations. Finally, we synthesised literature data across 49 species to assess broad trends and model environmental and biological drivers of anaesthetic response. AQUI-S induced anaesthesia rapidly but caused slower and more variable recovery, and slight declines in water pH. In contrast, 2-phenoxyethanol produced slower induction but offered faster, more consistent recovery, a broader safety margin (i.e., the difference between induction and euthanasia doses), and no measurable effect on water pH. Our multi-species models indicated that temperature and life history stage modulate AQUI-S responses, while pH influences the induction times of 2-phenoxyethanol. While both AQUI-S and 2-phenoxyethanol are effective anaesthetic agents, trade-offs between induction speed, recovery consistency, and environmental sensitivity can guide their optimal application for field research. Graphical abstract

Closure of the Strait of Hormuz may trigger a bioinvasion super-spreader event - Mario N. Tamburri; James T. Carlton; April M. H. Blakeslee; Alejandro Bortolus; João Canning-Clode; Susana Carvalho; Andrew L. Chang; Ian C. Davidson; Sarah C. Donelan; Lisa A. Drake; Amy E. Fowler; Amy L. Freestone; et al. (Biological Invasions, 2026)

Blowin’ in the wind: Onshore winds drive the occurrence of bluebottles (Physalia spp.) at east Australian beaches - Daniel E. Hewitt; Amandine Schaeffer; Jasmin C. Lawes; Sean Kelly; Alistair G.B. Poore; Moninya Roughan; Saima Ajaz; Timothy C. Ingleton; Kylie A. Pitt (Ocean & Coastal Management, 2026)

An in vitro-in silico workflow for predicting renal clearance of environmental chemicals and drugs - Courtney Sakolish; Hsing-Chieh Lin; Haley L. Moyer; Lucie C. Ford; Charles H. Christen; Barbara A. Wetmore; Michael J. DeVito; Philip Hewitt; Stephen S. Ferguson; Farah Raad; Ivan Rusyn; Weihsueh A. Chiu (Toxicology, 2026)

Active surveillance for influenza A virus in swine reveals within-farm reassortment and cocirculation of distinct subtypes and genetic clades - Megan N. Thomas; Garrett M. Janzen; Alexey Markin; Aditi Sharma; Kelly Hewitt; Ganwu Li; Amy L. Baker; Phillip C. Gauger; Tavis K. Anderson (Veterinary Microbiology, 2025)

P07-02 Safety evaluation of hair straightening products containing glyoxylic acid assessing formaldehyde release and oxalic acid formation - G. von Bölcsházy; N. Hewitt; C. Schmidt; S. Langhoff; C. Goebel (Toxicology Letters, 2025)

Evaluation of SARS-CoV-2 antibody detection methods for wild Cervidae - Joshua Hewitt; Grete Wilson-Henjum; Jeffrey C. Chandler; Aaron T. Phillips; Diego G. Diel; W. David Walter; Alec Baker; Jennifer Høy-Petersen; Guillaume Bastille-Rousseau; Tadao Kishimoto; George Wittemyer; Jeremy Alder; et al. (Preventive Veterinary Medicine, 2025)

Bismuth release from endodontic materials: Proposed mechanisms for systemic circulation and organ accumulation - Lauter Eston Pelepenko; Benjamin Hewitt; Rodrigo Bueno de Oliveira; Brenda Fornazaro Moraes; Débora C. Coraça-Huber; Ana Cristina Padilha Janini; Marina Angélica Marciano (Journal of Hazardous Materials, 2025)

Heat-set gelation of milk- and fermentation-derived β-lactoglobulin variants - Zheng Pan; Remco Kornet; Sheelagh Hewitt; Alan Welman; Jeremy P. Hill; Marcel Wubbolts; Stephen Mitchell; Warren C. McNabb; Aiqian Ye; Alejandra Acevedo-Fani; Skelte G. Anema (Food Hydrocolloids, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Aboveground-belowground linkages across vegetation degradation gradients differ among native eucalypt communities - Kumari Rajapaksha; Bryony Horton; Alison C. Hewitt; Jeff R. Powell; Uffe N. Nielsen; Yolima Carrillo (Science of The Total Environment, 2025)

Scale and ecosystem-based management: Navigating mismatches between socio-ecological systems - J. Ellis; E. Macpherson; S. Thrush; K. Fisher; C. Pilditch; E. Jorgensen; J. Low; F. Stephenson; A. Allison; S. Geange; J. Hewitt (Biological Conservation, 2025)

Long-term effects of an early-life exposure of fathead minnows to sediments containing bitumen. Part II: Behaviour, reproduction, and gonad histopathology - C. Vignet; R.A. Frank; C. Yang; K. Shires; M. Bree; C. Sullivan; W.P. Norwood; L.M. Hewitt; M.E. McMaster; J.L. Parrott (Environmental Pollution, 2024)

P19-32 Advancing the application of New Approach Methodologies (NAMs) in systemic toxicity assessment of cosmetic ingredients: insights from cosmetics Europe long range science strategy (2016–2022) case studies - C. Mahony; M. Baltazar; M. Dent; A. Giusti; N. Hewitt; G. Ouedraogo; A. Schepky (Toxicology Letters, 2024)

P06-09 Toxicogenomics to analyze systemic toxicity of salicylic acid as part of a NGRA ab initio case study - S. Voß; K. Brandmair; M. Böttcher; N.J. Hewitt; J. Kuehnl; C.-T. Krüger; D. Lange; J. Meinhardt; A. Najjar; A. Schepky; J. Ebmeyer (Toxicology Letters, 2024)

S10-01 Making safety decisions for a sunscreen active ingredient using next-generation risk assessment: benzophenone-4 case study - M.T. Baltazar; S. Cable; A. Punt; N.J. Hewitt; B. Nicol; P. Kukic; S. Scottt; S. Malcomber; R. Mascarenhas; C. Alexander-White; J. Reynolds; J. Houghton; et al. (Toxicology Letters, 2024)

The role of shade in influencing dung deposition and nutrient transfer by kangaroos (Macropus spp.) in an arid landscape - Sophie C. Hewitt; Keith Leggett; Mike Letnic (Journal of Arid Environments, 2024)

PMAxx-RT-qPCR to Determine Human Norovirus Inactivation Following High-Pressure Processing of Oysters - Andri Taruna Rachmadi; Pradip Gyawali; Graeme Summers; Anower Jabed; Graham C. Fletcher; Joanne Hewitt (Food and Environmental Virology, 2024)

Graphical Discrimination of New Zealand Honey from International Honey Using Elemental Analysis - Megan N. C. Grainger; Hannah Klaus; Nyssa Hewitt; Han Gan; Amanda D. French (Biological Trace Element Research, 2024)
This study investigated the potential of utilising the elemental fingerprinting of honey to differentiate New Zealand (NZ) honey from that of international origin. Twenty elements were analysed by ICP-MS in 352 honeys from 34 various countries. Of these, 323 honeys (245 New Zealand honeys, 78 international) and two subsets of data (NZ and European origin, n = 306, and, NZ and Denmark/Germany, n = 280) were visualised using principal component analysis (PCA). For the NZ/Europe subset, 42.2% of data was explained in the first two principal components. Statistical classification rules were also derived using linear discriminant analysis (LDA) and decision tree analysis. Various combinations of elements were explored for classification, considering the effect of soil-derived elements and those from anthropogenic sources. A high degree of accuracy (at least 90%) for the characterisation of New Zealand honey was observed for all statistical models, showing the robustness of these analyses. When using decision tree analysis to distinguish New Zealand samples from international samples, a tree with five terminal nodes (using Cs, Ba and Rb) was created with 92.4% accuracy. This work has demonstrated that elemental fingerprints of honey are a promising tool for categorising New Zealand honey from other geographical locations.

Root aphid (Aploneura lentisci) population size on perennial ryegrass is determined by drought and endophyte strain - Katrin G. Hewitt; Rainer W. Hofmann; Oliver J. Ball; Neil Cox; Racheal H. Bryant; Sarah C. Finch; Alison J. Popay (Journal of Pest Science, 2024)
Climate change is anticipated to lead to an increase in the occurrence and intensity of drought and fluctuations in insect cycles that will challenge modern pasture systems. Feeding by root aphids such as Aploneura lentisci Pass. can be a significant challenge to pastures. These below-ground living aphids are commonly found in New Zealand and Australia, feeding year-round on the roots of graminaceous plants such as perennial ryegrass ( Lolium perenne L.). Some strains of the fungal endophyte Epichloë festucae var. lolii in perennial ryegrass can provide protection against root aphids and greater resilience under drought, contributing to higher persistency and growth than endophyte-free plants. However, the interaction between insect pressure and drought is not understood. This study examined the effect of drought on root aphid populations and plant performance in perennial ryegrass plants relative to endophyte status (±) and endophyte strain (AR37, NZ CT ) in a glasshouse experiment. Plants were cloned across the drought and well-watered treatments, and half of the plants were inoculated with root aphids, whilst half of the plants were treated with insecticide. Endophyte infection with strain NZ CT and AR37 reduced root aphid numbers. Aphid populations were significantly higher in drought-stressed than in well-watered plants in both endophyte-infected and endophyte-free treatments. Under drought conditions, root aphid populations were increased 4-fold in NZ CT and 8-fold in AR37 and endophyte-free plants in comparison with their well-watered counterparts. Root aphids reduced shoot dry weight by 16% in drought-exposed and 26% in well-watered plants in comparison with their insecticide-treated counterparts whilst reducing root biomass by 49%. Our results suggest that root aphids are likely able to exploit the higher availability of amino acids in the plant sap of drought-exposed plants. This study provides evidence that climate change-mediated impacts of root aphids could reduce production in perennial ryegrass-dominant pastures. However, field trials would be necessary to determine whether this effect is seen in situ, where numerous additional factors will be operating at the same time.

S26-01: Evaluation of Microphysiological Systems combining skin models and systemic organs to elucidate the influence of application scenarios on the bioavailability, metabolic fate and biological effects of cosmetic chemicals - J. Kühnl; T.P. Tao; K. Brandmair; S. Gerlach; F. Kern; J. Przibilla; C. Genies; C. Jacques-Jamin; E. LeCluyse; E. Rogers; A. Schepky; U. Marx; et al. (Toxicology Letters, 2023)

Comparative techno-economic analysis of the integration of MEA-based scrubbing and silica PEI adsorbent-based CO2 capture processes into cement plants - M.M. Jaffar; C. Brandoni; J. Martinez; C. Snape; S. Kaldis; A. Rolfe; A. Santos; B. Lysiak; A. Lappas; N. Hewitt; Y. Huang (Journal of Cleaner Production, 2023)

Seasonal gain in body condition of foraging humpback whales along the Western Antarctic Peninsula - K. C. Bierlich; Joshua Hewitt; Robert S. Schick; Logan Pallin; Julian Dale; Ari S. Friedlaender; Fredrik Christiansen; Kate R. Sprogis; Allison H. Dawn; Clara N. Bird; Gregory D. Larsen; Ross Nichols; et al. (Frontiers in Marine Science, 2022)
Most baleen whales are capital breeders that use stored energy acquired on foraging grounds to finance the costs of migration and reproduction on breeding grounds. Body condition reflects past foraging success and can act as a proxy for individual fitness. Hence, monitoring the seasonal gain in body condition of baleen whales while on the foraging grounds can inform how marine mammals support the costs of migration, growth, and reproduction, as well as the nutritional health of the overall population. Here, we use photogrammetry from drone-based imagery to examine how the body condition of humpback whales ( Megaptera novaeangliae ) changed over the foraging season (November to June) along the Western Antarctic Peninsula (WAP) from 2017 to 2019. This population (IWC stock G) is recovering from past whaling and is growing rapidly, providing an opportunity to study how whales store energy in a prey-rich environment. We used a body area index (BAI) to estimate changes in body condition and applied a Bayesian approach to incorporate measurement uncertainty associated with different drone types used for data collection. We used biopsy samples to determine sex and pregnancy status, and a length-based maturity classification to assign reproductive classes ( n = 228; calves = 31, juveniles = 82, lactating females = 31, mature males = 12, mature unknown sex = 56, non-pregnant females = 12, pregnant females = 3, pregnant & lactating females = 1). Average BAI increased linearly over the feeding season for each reproductive class. Lactating females had lower BAI compared to other mature whales late in the season, reflecting the high energetic costs of nursing a calf. Mature males and non-pregnant females had the highest BAI values. Calves and juvenile whales exhibited an increase in BAI but not structural size (body length) over the feeding season. The body length of lactating mothers was positively correlated with the body length of their calves, but no relationship was observed between the BAI of mothers and their calves. Our study establishes a baseline for seasonal changes in the body condition for this humpback whale population, which can help monitor future impacts of disturbance and climate change.

Microbiome assembly in thawing permafrost and its feedbacks to climate - Jessica G. Ernakovich; Robyn A. Barbato; Virginia I. Rich; Christina Schädel; Rebecca E. Hewitt; Stacey J. Doherty; Emily D. Whalen; Benjamin W. Abbott; Jiri Barta; Christina Biasi; Chris L. Chabot; Jenni Hultman; et al. (Global Change Biology, 2022)
The physical and chemical changes that accompany permafrost thaw directly influence the microbial communities that mediate the decomposition of formerly frozen organic matter, leading to uncertainty in permafrost–climate feedbacks. Although changes to microbial metabolism and community structure are documented following thaw, the generality of post‐thaw assembly patterns across permafrost soils of the world remains uncertain, limiting our ability to predict biogeochemistry and microbial community responses to climate change. Based on our review of the Arctic microbiome, permafrost microbiology, and community ecology, we propose that Assembly Theory provides a framework to better understand thaw‐mediated microbiome changes and the implications for community function and climate feedbacks. This framework posits that the prevalence of deterministic or stochastic processes indicates whether the community is well‐suited to thrive in changing environmental conditions. We predict that on a short timescale and following high‐disturbance thaw (e.g., thermokarst), stochasticity dominates post‐thaw microbiome assembly, suggesting that functional predictions will be aided by detailed information about the microbiome. At a longer timescale and lower‐intensity disturbance (e.g., active layer deepening), deterministic processes likely dominate, making environmental parameters sufficient for predicting function. We propose that the contribution of stochastic and deterministic processes to post‐thaw microbiome assembly depends on the characteristics of the thaw disturbance, as well as characteristics of the microbial community, such as the ecological and phylogenetic breadth of functional guilds, their functional redundancy, and biotic interactions. These propagate across space and time, potentially providing a means for predicting the microbial forcing of greenhouse gas feedbacks to global climate change.

Barriers to coastal planning and policy use of environmental research in Aotearoa-New Zealand - Judi E. Hewitt; Carolyn J. Lundquist; Conrad A. Pilditch; Simon F. Thrush; Stephen C. Urlich (Frontiers in Marine Science, 2022)
Identifying barriers to the effective use of science in coastal management of Aotearoa-New Zealand is easy, due to the present lack of complicated governance and management structures, coupled with an emphasis on funding science that includes pathways to implementation. This opinion piece discusses four areas that still hinder effective use of science, all of which are likely to be problematic for other countries. We initially focus on why the science may not be used related to: misunderstandings (linguistic and conceptual differences including indigenous world views); timing of information delivery; uncertainty surrounding the information (knowledge limitations and funding); and top-down constraints (legal systems, politics and institutional objectives). We use Aotearoa-New Zealand examples to demonstrate the barriers operating within each area and discuss three potential solutions. Importantly our analysis indicates that researchers alone cannot transcend these barriers; rather, we need to work as part of an ecosystem, requiring commitment from all society, extending beyond the usual suspects (management agencies). We believe that ecological and systems education from junior school levels through to universities have an important role to play in setting the context to overcome current barriers.

Influence of offshore oil and gas structures on seascape ecological connectivity - Dianne L. McLean; Luciana C. Ferreira; Jessica A. Benthuysen; Karen J. Miller; Marie‐Lise Schläppy; Matthew J. Ajemian; Oliver Berry; Silvana N. R. Birchenough; Todd Bond; Fabio Boschetti; Ann S. Bull; Jeremy T. Claisse; et al. (Global Change Biology, 2022)
Offshore platforms, subsea pipelines, wells and related fixed structures supporting the oil and gas (O&G) industry are prevalent in oceans across the globe, with many approaching the end of their operational life and requiring decommissioning. Although structures can possess high ecological diversity and productivity, information on how they interact with broader ecological processes remains unclear. Here, we review the current state of knowledge on the role of O&G infrastructure in maintaining, altering or enhancing ecological connectivity with natural marine habitats. There is a paucity of studies on the subject with only 33 papers specifically targeting connectivity and O&G structures, although other studies provide important related information. Evidence for O&G structures facilitating vertical and horizontal seascape connectivity exists for larvae and mobile adult invertebrates, fish and megafauna; including threatened and commercially important species. The degree to which these structures represent a beneficial or detrimental net impact remains unclear, is complex and ultimately needs more research to determine the extent to which natural connectivity networks are conserved, enhanced or disrupted. We discuss the potential impacts of different decommissioning approaches on seascape connectivity and identify, through expert elicitation, critical knowledge gaps that, if addressed, may further inform decision making for the life cycle of O&G infrastructure, with relevance for other industries (e.g. renewables). The most highly ranked critical knowledge gap was a need to understand how O&G structures modify and influence the movement patterns of mobile species and dispersal stages of sessile marine species. Understanding how different decommissioning options affect species survival and movement was also highly ranked, as was understanding the extent to which O&G structures contribute to extending species distributions by providing rest stops, foraging habitat, and stepping stones. These questions could be addressed with further dedicated studies of animal movement in relation to structures using telemetry, molecular techniques and movement models. Our review and these priority questions provide a roadmap for advancing research needed to support evidence‐based decision making for decommissioning O&G infrastructure.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Comparing Uncertainty Associated With 1-, 2-, and 3D Aerial Photogrammetry-Based Body Condition Measurements of Baleen Whales - K. C. Bierlich; Joshua Hewitt; Clara N. Bird; Robert S. Schick; Ari Friedlaender; Leigh G. Torres; Julian Dale; Jeremy Goldbogen; Andrew J. Read; John Calambokidis; David W. Johnston (Frontiers in Marine Science, 2021)
Body condition is a crucial and indicative measure of an animal’s fitness, reflecting overall foraging success, habitat quality, and balance between energy intake and energetic investment toward growth, maintenance, and reproduction. Recently, drone-based photogrammetry has provided new opportunities to obtain body condition estimates of baleen whales in one, two or three dimensions (1D, 2D, and 3D, respectively) – a single width, a projected dorsal surface area, or a body volume measure, respectively. However, no study to date has yet compared variation among these methods and described how measurement uncertainty scales across these dimensions. This associated uncertainty may affect inference derived from these measurements, which can lead to misinterpretation of data, and lack of comparison across body condition measurements restricts comparison of results between studies. Here we develop a Bayesian statistical model using known-sized calibration objects to predict the length and width measurements of unknown-sized objects (e.g., a whale). We use the fitted model to predict and compare uncertainty associated with 1D, 2D, and 3D photogrammetry-based body condition measurements of blue, humpback, and Antarctic minke whales – three species of baleen whales with a range of body sizes. The model outputs a posterior predictive distribution of body condition measurements and allows for the construction of highest posterior density intervals to define measurement uncertainty. We find that uncertainty does not scale linearly across multi-dimensional measurements, with 2D and 3D uncertainty increasing by a factor of 1.45 and 1.76 compared to 1D, respectively. Each standardized body condition measurement is highly correlated with one another, yet 2D body area index (BAI) accounts for potential variation along the body for each species and was the most precise body condition metric. We hope this study will serve as a guide to help researchers select the most appropriate body condition measurement for their purposes and allow them to incorporate photogrammetric uncertainty associated with these measurements which, in turn, will facilitate comparison of results across studies.

Impact of ocean resolution and mean state on the rate of AMOC weakening - L. C. Jackson; M. J. Roberts; H. T. Hewitt; D. Iovino; T. Koenigk; V. L. Meccia; C. D. Roberts; Y. Ruprich-Robert; R. A. Wood (Climate Dynamics, 2020)
We examine the weakening of the Atlantic Meridional Overturning Circulation (AMOC) in response to increasing CO $$_2$$ 2 at different horizontal resolutions in a state-of-the-art climate model and in a small ensemble of models with differing resolutions. There is a strong influence of the ocean mean state on the AMOC weakening: models with a more saline western subpolar gyre have a greater formation of deep water there. This makes the AMOC more susceptible to weakening from an increase in CO $$_2$$ 2 since weakening ocean heat transports weaken the contrast between ocean and atmospheric temperatures and hence weaken the buoyancy loss. In models with a greater proportion of deep water formation further north (in the Greenland-Iceland-Norwegian basin), deep-water formation can be maintained by shifting further north to where there is a greater ocean-atmosphere temperature contrast. We show that ocean horizontal resolution can have an impact on the mean state, and hence AMOC weakening. In the models examined, those with higher resolutions tend to have a more westerly location of the North Atlantic Current and stronger subpolar gyre. This likely leads to a greater impact of the warm, saline subtropical Atlantic waters on the western subpolar gyre resulting in greater dense water formation there. Although there is some improvement of the higher resolution models over the lower resolution models in terms of the mean state, both still have biases and it is not clear which biases are the most important for influencing the AMOC strength and response to increasing CO $$_2$$ 2 .

Brown bullhead at the St. Lawrence River (Cornwall) Area of Concern: health and endocrine status in the context of tissue concentrations of PCBs and mercury - M. D. O. Pinheiro; D. B. D. Simmons; M. Villella; G. R. Tetreault; D. C. G. Muir; M. E. McMaster; L. M. Hewitt; J. L. Parrott; B. J. Park; S. B. Brown; J. P. Sherry (Environmental Monitoring and Assessment, 2020)

Impact of free-living pattern of sedentary behaviour on intra-day glucose regulation in type 2 diabetes - Aye C. Paing; Kathryn A. McMillan; Alison F. Kirk; Andrew Collier; Allan Hewitt; Sebastien F. M. Chastin (European Journal of Applied Physiology, 2020)
Purpose To investigate how the pattern of sedentary behaviour affects intra-day glucose regulation in type 2 diabetes. Methods This intensive longitudinal study was conducted in 37 participants with type 2 diabetes (age, 62.8 ± 10.5 years). Glucose and sedentary behaviour/physical activity were assessed with a continuous glucose monitoring (Abbott FreeStyle Libre) and an activity monitor (activPAL3) for 14 days. Multiple regression models with generalised estimating equations (GEEs) approach were used to assess the associations of sedentary time and breaks in sedentary time with pre-breakfast glucose, pre-lunch glucose, pre-dinner glucose, post-breakfast glucose, post-lunch glucose, post-dinner glucose, bedtime glucose, the dawn phenomenon, time in target glucose range (TIR, glucose 3.9–10 mmol/L) and time above target glucose range (TAR, glucose > 10 mmol/L). Results Sedentary time was associated with higher pre-breakfast glucose ( p = 0.001), pre-dinner glucose ( p < 0.001), post-lunch glucose ( p = 0.005), post-dinner glucose ( p = 0.013) and the dawn phenomenon ( p < 0.001). Breaks in sedentary time were associated with lower pre-breakfast glucose ( p = 0.023), pre-dinner glucose ( p = 0.023), post-breakfast glucose ( p < 0.001) and the dawn phenomenon ( p = 0.004). The association between sedentary time and less TIR ( p = 0.022) and the association between breaks in sedentary time and more TIR ( p = 0.001) were also observed. Conclusions Reducing sedentary time and promoting breaks in sedentary time could be clinically relevant to improve intra-day glucose regulation in type 2 diabetes.

Using green infrastructure to improve urban air quality (GI4AQ) - C. Nick Hewitt; Kirsti Ashworth; A. Rob MacKenzie (Ambio, 2020)

Automation in cell and gene therapy manufacturing: from past to future - P. Moutsatsou; J. Ochs; R. H. Schmitt; C. J. Hewitt; M. P. Hanga (Biotechnology Letters, 2019)
As more and more cell and gene therapies are being developed and with the increasing number of regulatory approvals being obtained, there is an emerging and pressing need for industrial translation. Process efficiency, associated cost drivers and regulatory requirements are issues that need to be addressed before industrialisation of cell and gene therapies can be established. Automation has the potential to address these issues and pave the way towards commercialisation and mass production as it has been the case for ‘classical’ production industries. This review provides an insight into how automation can help address the manufacturing issues arising from the development of large-scale manufacturing processes for modern cell and gene therapy. The existing automated technologies with applicability in cell and gene therapy manufacturing are summarized and evaluated here.

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

Growing Canopy on a College Campus: Understanding Urban Forest Change through Archival Records and Aerial Photography - Lara A. Roman; Jason P. Fristensky; Theodore S. Eisenman; Eric J. Greenfield; Robert E. Lundgren; Chloe E. Cerwinka; David A. Hewitt; Caitlin C. Welsh (Environmental Management, 2017)

A multicenter assessment of single-cell models aligned to standard measures of cell health for prediction of acute hepatotoxicity - Rowena L. Sison-Young; Volker M. Lauschke; Esther Johann; Eliane Alexandre; Sébastien Antherieu; Hélène Aerts; Helga H. J. Gerets; Gilles Labbe; Delphine Hoët; Martina Dorau; Christopher A. Schofield; Cerys A. Lovatt; et al. (Archives of Toxicology, 2017)

Science and Societal Partnerships to Address Cumulative Impacts - Carolyn J. Lundquist; Karen T. Fisher; Richard Le Heron; Nick I. Lewis; Joanne I. Ellis; Judi E. Hewitt; Alison J. Greenaway; Katie J. Cartner; Tracey C. Burgess-Jones; David R. Schiel; Simon F. Thrush (Frontiers in Marine Science, 2016)

Seasonal climatic variations influence the efficacy of predatory mites used for control of western flower thrips in greenhouse ornamental crops - Laura C. Hewitt; Les Shipp; Rose Buitenhuis; Cynthia Scott-Dupree (Experimental and Applied Acarology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Multiparameter flow cytometry for the characterisation of extracellular markers on human mesenchymal stem cells - Alexander K. C. Chan; Thomas R. J. Heathman; Karen Coopman; Christopher J. Hewitt (Biotechnology Letters, 2014)

The effects of aggressive mitigation on steric sea level rise and sea ice changes - J. Körper; I. Höschel; J. A. Lowe; C. D. Hewitt; D. Salas y Melia; E. Roeckner; H. Huebener; J.-F. Royer; J.-L. Dufresne; A. Pardaens; M. A. Giorgetta; M. G. Sanderson; et al. (Climate Dynamics, 2013)

Biophysical patterns in benthic assemblage composition across contrasting continental margins off New Zealand - Tanya J. Compton; David A. Bowden; C. Roland Pitcher; Judi E. Hewitt; Nick Ellis (Journal of Biogeography, 2013)
Aim To examine whether benthic assemblages are more diverse in a region of high topographic and oceanographic complexity by comparing benthic invertebrate assemblages across continental margins with contrasting environments. Location Challenger Plateau and Chatham Rise, to the west and east of New Zealand, respectively. Methods Benthic faunal data were sourced from extensive seabed surveys in 2007, when both margins were sampled with an epibenthic sled and a towed video system. Three methods were used to investigate benthic assemblages in relation to environmental variables: one based on individual species distribution models ( SDM s) using boosted regression trees analysis ( BRT ), and two community‐based modelling methods using generalized dissimilarity modelling ( GDM ) and gradient forest analysis ( GF ), respectively. Each method was used to model and predict the turnover in assemblages with respect to environment – the ‘biophysical patterns’ – across the study region. Results Across Chatham Rise, a complex oceanographic environment arising from steep gradients in productivity and temperature at the Subtropical Front produced a high diversity of assemblages associated with the sub‐Antarctic water mass, the Subtropical Front, steep‐sloping regions and fast tidal currents. In contrast, Challenger Plateau lies entirely beneath a single (subtropical) water mass, and assemblage diversity was lower, with a distinctive assemblage on the plateau itself and a deep‐water assemblage similar to the northern deep‐water assemblage of Chatham Rise. Across both regions, assemblage turnover was fastest in cold waters, at shallow depths and in deep mixed layers. Main conclusions Benthic assemblages were more varied on Chatham Rise than on Challenger Plateau, supporting the hypothesis that environmentally heterogeneous margins have higher assemblage diversity. Differing assemblages on the northern and southern flanks of Chatham Rise suggest a biogeographical boundary for benthic taxa across the Subtropical Front. These results demonstrate that oceanographically and topographically complex margins have a diverse assemblage structure that should be considered in planning for the sustainable management of diversity.

Rapid identification of novel functional promoters for gene therapy - Ian A. Pringle; Deborah R. Gill; Mary M. Connolly; Anna E. Lawton; Anne-Marie Hewitt; Graciela Nunez-Alonso; Seng H. Cheng; Ronald K. Scheule; Lee A. Davies; Stephen C. Hyde (Journal of Molecular Medicine, 2012)

Plant pest and disease diagnosis using electronic nose and support vector machine approach - Reza Ghaffari; Jullada Laothawornkitkul; Daciana Iliescu; Evor Hines; Mark Leeson; Richard Napier; Jason P Moore; Nigel D Paul; C Nicholas Hewitt; Jane E Taylor (Journal of Plant Diseases and Protection, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Numts help to reconstruct the demographic history of the ocellated lizard ( Lacerta lepida ) in a secondary contact zone - ANDREIA MIRALDO; GODFREY M. HEWITT; PAUL H. DEAR; OCTAVIO S. PAULO; BRENT C. EMERSON (Molecular Ecology, 2012)
In northwestern Iberia, two largely allopatric Lacerta lepida mitochondrial lineages occur, L5 occurring to the south of Douro River and L3 to the north, with a zone of putative secondary contact in the region of the Douro River valley. Cytochrome b sequence chromatograms with polymorphisms at nucleotide sites diagnostic for the two lineages were detected in individuals in the region of the Douro River and further north within the range of L3. We show that these polymorphisms are caused by the presence of four different numts (I–IV) co‐occurring with the L3 genome, together with low levels of heteroplasmy. Two of the numts (I and II) are similar to the mitochondrial genome of L5 but are quite divergent from the mitochondrial genome of L3 where they occur. We show that these numts are derived from the mitochondrial genome of L5 and were incorporated in L3 through hybridization at the time of secondary contact between the lineages. The additional incidence of these numts to the north of the putative contact zone is consistent with an earlier postglacial northward range expansion of L5, preceding that of L3. We show that genetic exchange between the lineages responsible for the origin of these numts in L3 after secondary contact occurred prior to, or coincident with, the northward expansion of L3. This study shows that, in the context of phylogeographic analysis, numts can provide evidence for past demographic events and can be useful tools for the reconstruction of complex evolutionary histories.

Climate change under aggressive mitigation: the ENSEMBLES multi-model experiment - T. C. Johns; J.-F. Royer; I. Höschel; H. Huebener; E. Roeckner; E. Manzini; W. May; J.-L. Dufresne; O. H. Otterå; D. P. van Vuuren; D. Salas y Melia; M. A. Giorgetta; et al. (Climate Dynamics, 2011)

Erratum to: Climate change under aggressive mitigation: the ENSEMBLES multi-model experiment - T. C. Johns; J.-F. Royer; I. Höschel; H. Huebener; E. Roeckner; E. Manzini; W. May; J.-L. Dufresne; O. H. Otterå; D. P. van Vuuren; D. Salas y Melia; M. A. Giorgetta; et al. (Climate Dynamics, 2011)

Wild Turkey (Meleagris gallopavo) association to roads: implications for distance sampling - Devin R. Erxleben; Matthew J. Butler; Warren B. Ballard; Mark C. Wallace; Markus J. Peterson; Nova J. Silvy; William P. Kuvlesky; David G. Hewitt; Stephen J. DeMaso; Jason B. Hardin; Megan K. Dominguez-Brazil (European Journal of Wildlife Research, 2011)

Reproductive phenology of the introduced kelp Undaria pinnatifida (Phaeophyceae, Laminariales) in Port Phillip Bay (Victoria, Australia) - C. Primo; C. L. Hewitt; M. L. Campbell (Biological Invasions, 2010)

Genetic structure and regulation of isoprene synthase in Poplar (Populus spp.) - Claudia E. Vickers; Malcolm Possell; C. Nicholas Hewitt; Philip M. Mullineaux (Plant Molecular Biology, 2010)

Effects of fosmidomycin on plant photosynthesis as measured by gas exchange and chlorophyll fluorescence - Malcolm Possell; Annette Ryan; Claudia E. Vickers; Philip M. Mullineaux; C. Nicholas Hewitt (Photosynthesis Research, 2010)

Modelling chemistry in the nocturnal boundary layer above tropical rainforest and a generalised effective nocturnal ozone deposition velocity for sub-ppbv NOx conditions - Thomas A. M. Pugh; James Ryder; A. Robert MacKenzie; Sarah J. Moller; James D. Lee; Carole Helfter; Eiko Nemitz; Douglas Lowe; C. Nicholas Hewitt (Journal of Atmospheric Chemistry, 2010)

Investigation of first year biotic and abiotic influences on the recruitment of pike Esox lucius over 48 years in Windermere, U.K. - C. G. M. Paxton; I. J. Winfield; J. M. Fletcher; D. G. George; D. P. Hewitt (Journal of Fish Biology, 2009)
Estimated pike Esox lucius recruitment varied by a factor of 16 for females from 1944 to 1991 and by a factor of 27 for males from 1943 to 1990 in Windermere, a temperate, mesotrophic U.K. lake. No significant stock–recruitment relationships were found, but analysis with general additive models (GAMs) revealed that early autumnal water temperature, strength and direction of the North Atlantic Oscillation displacement (corresponding to different climatic conditions in winter) and zooplankton abundance but above all, late summer water temperature were important explanatory variables over the entire time series. Female recruitment was also influenced by young‐of‐the‐year winter temperature. There was no evidence that perch Perca fluviatilis year‐class strength, lake level or the summer position of the Gulf Stream influenced recruitment. The fitted models explained up to c. 65% of the overall observed variation between years.

A comparison of PMIP2 model simulations and the MARGO proxy reconstruction for tropical sea surface temperatures at last glacial maximum - Bette L. Otto-Bliesner; Ralph Schneider; E. C. Brady; M. Kucera; A. Abe-Ouchi; E. Bard; P. Braconnot; M. Crucifix; C. D. Hewitt; M. Kageyama; O. Marti; A. Paul; et al. (Climate Dynamics, 2009)

Gas exchange and photosynthetic performance of the tropical tree Acacia nigrescens when grown in different CO2 concentrations - Malcolm Possell; C. Nicholas Hewitt (Planta, 2009)

The Southern Westerlies during the last glacial maximum in PMIP2 simulations - Maisa Rojas; Patricio Moreno; Masa Kageyama; Michel Crucifix; Chris Hewitt; Ayako Abe-Ouchi; Rumi Ohgaito; Esther C. Brady; Pandora Hope (Climate Dynamics, 2009)

Evaluation of coupled ocean–atmosphere simulations of the mid-Holocene using palaeovegetation data from the northern hemisphere extratropics - J. Wohlfahrt; S. P. Harrison; P. Braconnot; C. D. Hewitt; A. Kitoh; U. Mikolajewicz; B. L. Otto-Bliesner; S. L. Weber (Climate Dynamics, 2008)

Apparent autosomal dominant keratoconus in a large Australian pedigree accounted for by digenic inheritance of two novel loci - Kathryn P. Burdon; Douglas J. Coster; Jac C. Charlesworth; Richard A. Mills; Kate J. Laurie; Cecilia Giunta; Alex W. Hewitt; Paul Latimer; Jamie E. Craig (Human Genetics, 2008)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Apparent ‘sympatric’ speciation in ecologically similar herbivorous beetles facilitated by multiple colonizations of an island - BJARTE H. JORDAL; BRENT C. EMERSON; GODFREY M. HEWITT (Molecular Ecology, 2006)
Coexistence of recently diverged and ecologically similar sister species in complete sympatry represents a particularly compelling case for sympatric speciation. This study investigates the possible sympatric origin of two coexisting bark beetle taxa that utilize the same host plant on the island of La Palma in the Canary Islands. Aphanarthrum subglabrum and Aphanarthrum glabrum ssp. nudum breed inside dead twigs of Euphorbia lamarckii plants and are closely related to the allopatric A. glabrum ssp. glabrum in Tenerife, El Hierro and La Gomera. We tested the various speciation hypotheses in a genealogical context, using mitochondrial gene fragments from Cytochrome Oxidase I and 16S, and nuclear gene fragments from Enolase , Elongation Factor 1α and Histone H3. Phylogenetic analyses of the combined nuclear DNA data strongly supported a sister relationship between two sympatric and reproductively isolated taxa in La Palma. However, network analyses of subdivided nonrecombinant segments of the Enolase locus indicated a closer relationship between the two allopatric A. glabrum subspecies, suggesting multiple colonizations of this island. A bimodal distribution of mtDNA haplotypes in La Palma further documented the independent colonization of this island, with asymmetric introgression of mtDNA between two lineages. Consequently, the sympatric origin of the La Palma species is concluded to have involved allopatric phases before the parallel colonization of this island and subsequent introgression at some loci. The clear genetic and morphological evidence for reproductive isolation between these species suggests that the sympatric completion of divergence was either due to initial genetic incompatibility, morphological character displacement in male genitalia, or a combination of these factors.

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Northern Rivers Ecosystem Initiative: Distribution and Effects of Contaminants - M. E. Mcmaster; M. S. Evans; M. Alaee; D. C. G. Muir; L. M. Hewitt (Environmental Monitoring and Assessment, 2006)

Wolbachia and other endosymbiont infections in spiders - SARA L. GOODACRE; OLIVER Y. MARTIN; C. F. GEORGE THOMAS; GODFREY M. HEWITT (Molecular Ecology, 2006)
Maternally inherited endosymbiotic bacteria, such as Wolbachia , Rickettsia and Spiroplasma , have been shown to have wide‐ranging effects on the reproduction of their hosts. We present data on the presence of each of these sorts of bacteria in spiders, a group for which there are currently few data, but where such infections could explain many observed reproductive characteristics, such as sex ratio skew. The Wolbachia and Spiroplasma variants that we find in spiders belong to the same clades previously found to infect other arthropods, but many of the rickettsias belong to two, novel, hitherto spider‐specific bacterial lineages. We find evidence for coexistence of different bacterial types within species, and in some cases, within individuals. We suggest that spiders present a useful opportunity for studying the effect of these sorts of bacteria on the evolution of host traits, such as those that are under sexual selection.

A multi-model analysis of the role of the ocean on the African and Indian monsoon during the mid-Holocene - Y. Zhao; P. Braconnot; O. Marti; S.P. Harrison; C. Hewitt; A. Kitoh; Z. Liu; U. Mikolajewicz; B. Otto-Bliesner; S.L. Weber (Climate Dynamics, 2005)

Behavioural and pharmacological magnetic resonance imaging assessment of the effects of methylphenidate in a potential new rat model of attention deficit hyperactivity disorder - Katherine N. Hewitt; Yasmene B. Shah; Malcolm J. W. Prior; Peter G. Morris; Chris P. Hollis; Kevin C. F. Fone; Charles A. Marsden (Psychopharmacology, 2005)

The effects of glacial atmospheric CO 2 concentrations and climate on isoprene emissions by vascular plants - Malcolm Possell; C. Nicholas Hewitt; David J. Beerling (Global Change Biology, 2005)
Isoprene (C 5 H 8 ) emissions by terrestrial vegetation vary with temperature and light intensity, and play an important role in biosphere–chemistry–climate interactions. Such interactions were probably substantially modified by Pleistocene climate and CO 2 cycles. Central to understanding the nature of these modifications is assessment and analysis of how emissions changed under glacial environmental conditions. Currently, even the net direction of change is difficult to predict because a CO 2 ‐depleted atmosphere may have stimulated emissions compensating for the negative impacts of a cooler climate. Here, we address this issue and attempt to determine the direction of change from an experimental standpoint by investigating the interaction between isoprene emissions and plant growth of two known isoprene‐emitting herbaceous species ( Mucuna pruriens and Arundo donax ) grown at glacial (180 ppm) to present (366 ppm) CO 2 levels. We found a significant enhancement of isoprene emissions per unit leaf area in M. pruriens under subambient CO 2 concentrations relative to ambient controls but not for A. donax . In contrast, canopy emissions remained unaltered for both plant species because enhanced leaf emissions were offset by reductions in biomass and leaf area. Separate growth experiments with M. pruriens revealed that lowering day/night temperatures by 5°C decreased canopy isoprene emissions irrespective of the CO 2 level. Incorporation of these results into a simple canopy emissions model highlights their potential to attenuate reductions in the total isoprene flux from forests under glacial conditions predicted by standard models.

Biotic and abiotic influences on the recruitment of male perch in Windermere, U.K. - C. G. M. Paxton; I. J. Winfield; J. M. Fletcher; D. G. George; D. P. Hewitt (Journal of Fish Biology, 2004)
Perch Perca fluviatilis recruitment (based on the catch per unit effort, CPUE, of 2 or 3 year male perch) varied greatly from 1941 to 1995 in Windermere, U.K., with year class strengths strongly synchronous between the two basins of this temperate, mesotrophic lake. Statistically significant modified Ricker (Saila‐Lorda) stock‐recruitment curves could be fitted to data from three of four sampling sites, while the presence of widespread disease and late summer water temperature were also important explanatory variables. Multiple‐regression analyses revealed no influences of pike Esox lucius recruitment, zooplankton abundance, or the climatic influences ( i.e . North Atlantic Oscillation and displacement of the summer position of the Gulf Stream) on perch recruitment over and above associated influences from temperature. Fitted models realistically explained up to c . 60% of the observed variation in perch recruitment.

Interactive effects of elevated CO 2 and soil fertility on isoprene emissions from Quercus robur - Malcolm Possell; James Heath; C. Nicholas Hewitt; Edward Ayres; Gerhard Kerstiens (Global Change Biology, 2004)
The effects of global change on the emission rates of isoprene from plants are not clear. A factor that can influence the response of isoprene emission to elevated CO 2 concentrations is the availability of nutrients. Isoprene emission rate under standard conditions (leaf temperature: 30°C, photosynthetically active radiation (PAR): 1000 μmol photons m −2 s −1 ), photosynthesis, photosynthetic capacity, and leaf nitrogen (N) content were measured in Quercus robur grown in well‐ventilated greenhouses at ambient and elevated CO 2 (ambient plus 300 ppm) and two different soil fertilities. The results show that elevated CO 2 enhanced photosynthesis but leaf respiration rates were not affected by either the CO 2 or nutrient treatments. Isoprene emission rates and photosynthetic capacity were found to decrease with elevated CO 2 , but an increase in nutrient availability had the converse effect. Leaf N content was significantly greater with increased nutrient availability, but unaffected by CO 2 . Isoprene emission rates measured under these conditions were strongly correlated with photosynthetic capacity across the range of different treatments. This suggests that the effects of CO 2 and nutrient levels on allocation of carbon to isoprene production and emission under near‐saturating light largely depend on the effects on photosynthetic electron transport capacity.

Towards a mutant map of the mouse ? new models of neurological, behavioural, deafness, bone, renal and blood disorders - Sohaila Rastan; Tertius Hough; Amy Kierman; Rachel Hardisty; Alexandra Erven; Ian C. Gray; Stepanie Voeling; Adrian Isaacs; Hsun Tsai; Mark Strivens; Rebecca Washbourne; Claire Thornton; et al. (Genetica, 2004)

Interaction and impacts of two introduced species on a soft-sediment marine assemblage in SE Tasmania - D. J. Ross; C. R. Johnson; C. L. Hewitt; G. M. Ruiz (Marine Biology, 2004)

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

The effect of ocean dynamics in a coupled GCM simulation of the Last Glacial Maximum - C. Hewitt; R. Stouffer; A. Broccoli; J. Mitchell; Paul J. Valdes (Climate Dynamics, 2003)

Invasion success: does size really matter? - A. W. Miller; C. L. Hewitt; G. M. Ruiz (Ecology Letters, 2002)
The recent paper by Roy et al . (2001) presents a compelling relationship between range limit shifts, climatic fluctuations, and body size for marine bivalves in the fossil record. However, their extension of body size as a correlate for contemporary marine bivalve introductions is problematic and requires further scrutiny. Unlike their analysis of the fossil assemblage, the approach used for contemporary invasions does not adequately control for dispersal mechanism (vector) or source region. First, their analysis included mariculture species, intentionally introduced because of their large size, creating a vector‐specific bias. Second, successful invaders from multiple source regions (Northern Hemisphere) were compared with potential invaders from a single source region (north‐eastern Pacific), leaving both source and vector as uncontrolled variables. We present an analysis of body size for bivalve introductions from a single vector and source region, indicating no correlation between body size and invasion success when eliminating intentional introduction, source region and transport vector as confounding factors.

Influence of Transport over a Mountain Ridge on the Chemical Composition of Marine Aerosols during the ACE-2 Hillcloud Experiment - A. G. Allen; B. M. Davison; J. D. James; L. Robertson; R. M. Harrison; C. N. Hewitt (Journal of Atmospheric Chemistry, 2002)

Phylogenetic relationships among the Canary Island Steganacaridae (Acari, Oribatida) inferred from mitochondrial DNA sequence data - N Salomone; B. C Emerson; G. M Hewitt; F Bernini (Molecular Ecology, 2002)
The mite genus Steganacarus is represented in the Canary Islands by three endemic species, one recently discovered species, and several morphotypes of uncertain taxonomic position. We used a fragment of the mitochondrial cytochrome oxidase I gene to reconstruct the phylogenetic relationships among representatives of the different taxa from the three central islands of the archipelago, Tenerife, La Gomera and Gran Canaria. Sequence data were analysed by both maximum parsimony and maximum likelihood methods. The inferred phylogenetic relationships do not correlate well with current morphological taxonomy but reveal four deeply divergent and geographically coherent lineages, one each on Gran Canaria and La Gomera and two on Tenerife. No pattern of molecular differentiation was observed among different morphotypes. Possible explanations for this incongruence are suggested in relation to the ecology and biogeography of the group. A recently discovered Steganacarus species from La Gomera, morphologically quite distinct from the other Canarian Steganacarus , is clearly identified as a taxon distantly related to all the other Canarian samples.

The impact of dynamic sea-ice on the climatology and climate sensitivity of a GCM: a study of past, present, and future climates - C. D. Hewitt; C. A. Senior; J. F. B. Mitchell (Climate Dynamics, 2001)

Mitochondrial DNA, ecology and morphology: interpreting the phylogeography of the Nesotes (Coleoptera: Tenebrionidae) of Gran Canaria (Canary Islands) - D. J. Rees; B. C. Emerson; P. Oromí; G. M. Hewitt (Molecular Ecology, 2001)
The genus Nesotes (Coleoptera: Tenebrionidae) is represented in the Canary Islands by 19 endemic species, the majority of which are single island endemics. Nesotes conformis and N. fusculus are described on four and three islands, respectively, but each forms a paraphyletic assemblage between Gran Canaria and the other islands. The other described species for Gran Canaria are N. quadratus , N. lindbergi and N. piliger . Thirty‐six individuals representing the five species on Gran Canaria have been sequenced for 675 bp of the mitochondrial DNA (mtDNA) cytochrome oxidase II gene. Neighbour‐joining analysis of maximum likelihood distances resulted in five distinct mtDNA lineages for N. quadratus , two of which also include mitotypes of N. conformis . Each of the other three species is found on only one mtDNA lineage. We propose from the molecular data that differentiation in a widespread N. quadratus ‐type ancestor was followed by morphological adaptation to coastal, pine and laurel forest habitats.

Evidence for male‐biased dispersal in Lake Malawi cichlids from microsatellites - M. E. Knight; M. J. H. van Oppen; H. L. Smith; C. Rico; G. M. Hewitt; G. F. Turner (Molecular Ecology, 1999)
This study addressed within‐population dispersal patterns among the species‐rich Lake Malawi cichlids, specifically among the rock‐dwelling mbuna group. Relatedness values were calculated for 160 individuals belonging to two species from known locations in the field by screening six highly polymorphic microsatellite loci. The results from both species indicate that spatially adjacent females have higher average relatedness values than those separated by larger distances, but that this pattern is reversed in males. This therefore provides firm evidence for male‐biased dispersal within the Malawian cichlid flock.

Isolation and characterization of microsatellite loci in European hake, Merlucius merlucius (Merlucidae, Teleostei) - P. Morán; C. Lundy; C. Rico; G. M. Hewitt (Molecular Ecology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Fine‐scale genetic structuring in a natural population of European wild rabbits ( Oryctolagus cuniculus ) - A. K. SURRIDGE; K. M. IBRAHIM; D. J. BELL; N. J. WEBB; C. RICO; G. M. HEWITT (Molecular Ecology, 1999)
The genetic structure of a free‐living tagged population of European wild rabbits ( Oryctolagus cuniculus ) was investigated for two consecutive years (1990 and 1991) using 10 polymorphic microsatellite loci. A specific social behaviour, the formation of stable breeding groups, influenced the genetic structure of the population. These breeding groups were shown to constitute genetically differentiated units with low levels of gene flow between them. The average relatedness among members of a social group was higher than within the population as a whole. As a result of female philopatry coupled with male‐biased natal dispersal, the relatedness of females was higher than that of males, both within social groups and in the whole population. Furthermore, the average relatedness of females within groups was twice the relatedness of females between groups. This study reveals marked fine‐scale, intrapopulation genetic structure, which is attributable to the social behaviour of the European wild rabbit.

Microsatellite paternity analysis on captive Lake Malawi cichlids supports reproductive isolation by direct mate choice - M. E. KNIGHT; G. F. TURNER; C. RICO; M. J. H. VAN OPPEN; G. M. HEWITT (Molecular Ecology, 1998)
Three sympatrically occurring members of a cichlid fish species complex from Lake Malawi have previously been reported to show assortative mating in the field. Offspring from three experimental tanks each housing both sexes of all three members of this complex were screened at one to four microsatellite loci to determine paternity. Reproductive isolation was found to persist without exception under laboratory conditions, providing strong evidence for behavioural barriers to mating. Direct mate choice is suggested as the process preventing interbreeding. The results are interpreted with reference to the rapid and explosive evolution of the cichlid group.

In Vivo Bioavailability and Metabolism of Topical Diclofenac Lotion in Human Volunteers - Xiaoying Hui; Philip G. Hewitt; Nicholas Poblete; Howard I. Maibach; J. Zev Shainhouse; Ronald C. Wester (Pharmaceutical Research, 1998)

Mitochondrial DNA phylogeography of European hedgehogs - F. SANTUCCI; B. C. EMERSON; G. M. HEWITT (Molecular Ecology, 1998)
European hedgehog populations belonging to Erinaceus europaeus and E . concolor have been investigated by mitochondrial DNA analysis. A 383 bp fragment of the cytochrome b gene has been sequenced and maximum parsimony and neighbour‐joining trees of Tamura–Nei genetic distance values have been constructed. Similar topologies have been produced by both methods, showing a deep divergence between E . europaeus and E . concolor and a further subdivision of each species into a western and an eastern clade. A comparison with previously published allozyme data is made, and concordant and discordant patterns are discussed. The influence of Pleistocene glaciations on the observed pattern of divergence is inferred.

Assortative mating among rock‐dwelling cichlid fishes supports high estimates of species richness from Lake Malawi - MADELEINE J. H. VAN OPPEN; GEORGE F. TURNER; CIRO RICO; ROSANNA L. ROBINSON; JAMES C. DEUTSCH; MARTIN J. GENNER; GODFREY M. HEWITT (Molecular Ecology, 1998)
It has been estimated that Lake Malawi, Africa, contains 500–650 endemic species of cichlid fishes, the largest number of vertebrate species endemic to any comparable sized area on the planet. As many of these putative species cannot be distinguished anatomically, these estimates of species richness depend to a great extent on the assumption that sympatrically occurring male colour morphs represent biological species. We have tested this assumption using a combination of behavioural observations of courtship and microsatellite DNA analysis for six putative species of the Pseudotropheus ( Tropheops ) complex and three of the Pseudotropheus ( Maylandia ) complex occurring sympatrically at Nkhata Bay. We were unable to demonstrate assortative courtship for the species pairs Pseudotropheus ( Maylandia ) zebra / P . ‘gold zebra’ or P. ( Tropheops ) ‘band’/ P. ( T .) ‘rust’ because we were unable to distinguish between the females of these taxa. All other taxa showed clear assortative courtship, except for P. ( T .) ‘deep’, a deep‐water species which was rarely observed. Fixation indices (θ ST for the infinite allele model, and R ST for the stepwise mutation model) calculated from six microsatellite DNA loci demonstrated significant deviations from panmixia in all pairwise comparisons of putative species, indicating little or no gene flow between populations. All taxa showed high levels of allelic diversity providing evidence that genetic bottlenecking may have been of limited importance in the speciation process. Assortative mating among taxa differing only in male colouration is supportive of theories that speciation in these fishes has been driven by sexual selection by female choice.

In Vitro Cutaneous Disposition of a Topical Diclofenac Lotion in Human Skin: Effect of a Multi-Dose Regimen - Philip G. Hewitt; Nicholas Poblete; Ronald C. Wester; Howard I. Maibach; J. Zev Shainhouse (Pharmaceutical Research, 1998)

Responses of the phytoplankton to a deliberate attempt to raise the trophic status of an acidic, oligotrophic mountain lake - C. S. Reynolds; G. H. M. Jaworski; J. V. Roscoe; D. P. Hewitt; D. G. George (Hydrobiologia, 1998)

Radiative forcing and response of a GCM to ice age boundary conditions: cloud feedback and climate sensitivity - C. D. Hewitt; J. F. B. Mitchell (Climate Dynamics, 1997)

Stock composition in North Atlantic populations of whiting using microsatellite markers - C. Rico; K. M. Ibrahim; I. Rico; G. M. Hewitt (Journal of Fish Biology, 1997)
A size‐selected library constructed from DNA of the whiting Merlangius merlangus was screened. From about 3200 recombinant clones, 43 microsatellite loci were detected. Thirteen were sequenced in full. Primers were designed from the sequence of the flanking regions for six loci and used to test the allelic variability at these loci using the polymerase chain reaction (PCR). In addition, five primer pairs developed for the stickleback and another seven for cod were tested. Only six primer pairs revealed at least three alleles per locus. The three useful loci Gmo2, Mmer‐ UEAW01 and Mmer‐ UEAW02, had 14–23 alleles per locus in 370 samples. Estimates of genetic structure (φ) were not statistically significant. However, estimates of genetic differentiation ( F st ) were significantly different from zero. Heterogeneity χ 2 ‐analysis of allele frequencies among populations suggested relatively low levels of differentiation among samples. Significantly different allele frequency distributions were found for Borgensfjord and northern and southern North Sea samples for at least one locus, and between the latter samples for Mmer ‐UEAW02 and Gmo2 . There were significant excesses of homozygotes in all samples, over expectation for randomly mating populations in Hardy‐Weinberg equilibrium. The estimated frequencies of null alleles were 14.3%, for Mmer ‐UEAW01, 10.2% for Mmer‐ UEAW02 and 11.6% for Gmo2 . This result calls for a careful interpretation of the significance of these microsatellite data.

The mouse homolog of FRG1, a candidate gene for FSHD, maps proximal to the myodystrophy mutation on chromosome 8 - Prabhjit K. Grewal; Judith C. T. van Deutekom; Kate A. Mills; Richard J. L. F. Lemmers; Kathy D. Mathews; Rune R. Frants; Jane E. Hewitt (Mammalian Genome, 1997)

Isolation and characterization of microsatellite loci in the cichlid fish Pseudotropheus zebra - M. J. H. Van Oppen; C. Rico; J. C. Deutsch; G. F. Turner; G. M. Hewitt (Molecular Ecology, 1997)